THE EFFECT OF COMPANY'S SIZE, INDUSTRIAL TYPE, PROFITABILITY, AND LEVERAGE TO SUSTAINABILITY REPORT DISCLOSURE - Wanti Karlina; Sri Mulyati; Trisandi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Companies that reveal sustainability reports from year to year are increasing, but the number of companies is still far behind companies that do not discloes. To encourage companies to create sustainability reports, the National Center for Sustainability Reporting (NCSR) holds the annual Sustainability Reporting Award (SRA) that have been held since 2005. This study was conducted to determine the effect of company's size, industry type, profitability, and leverage on disclosure of sustainability report. The population used in this study are companies listed in the Sustainability Reporting Award (SRA). The technique of selecting sample is using purposive sampling.Sample according to the criteria obtained 20 companies during the observation period 2014-2016. Analyzing used in this research is multiple regression and hypothesis test using t test, f test, and coefficient of determination. The results of this study indicate that industry type and leverage variables affect the disclosure sustainability report. While the variable size of the company, and profitability does not affect the disclosure sustainability report.